SED693 : Issues in physical and health education / Faculty of Education - UiTM, Faculty of Education
This course is designed for students to engage with a wide range of issues related to teaching Physical and Health education. This course practising students to reflect on issues important to improving teaching in physical education. It encourages reflection and debate of the students to consider and reflect on issues so that they can make reasoned and informed judgement about the topic discussed.